Incorporating consumer choice into an optimization model for the German heat sector: Effects on projected bioenergy use. (1st May 2021) - Jordan, Matthias; Hopfe, Charlotte; Millinger, Markus; Rode, Julian; Thrän, Daniela
Abstract: The energy transition requires policy makers to adopt a holistic view that also considers non-economic factors when developing cleaner technology deployment schemes. In particular, a broad knowledge base is required to ensure an efficient energetic use of the limited biomass potential. Energy system optimization models are widely used to inform decision makers about energy transition strategies. The heterogeneity of consumers, especially in the heat sector, is rarely considered in these models and therefore these models lack of completion to contribute to this holistic approach. In this study, a literature review was conducted to find empirical data on consumer behavior regarding the adoption of residential heating systems. This data was integrated into an optimization model for the German heat sector, combining established methods for integrating consumer heterogeneity with a novel approach for calculating indirect costs representing behavioral factors. The incorporation of consumer choice leads to a broader distribution of market shares of different technologies in both a "business-as-usual" scenario and an "ambitious measures" scenario. In particular, the future role of log wood technologies in the private household sector may have been underestimated in previous studies and should be discussed, when designing policies. With this study, the knowledge base for decision makers was extended to discuss the future efficient use of biomass within the German heat sector. Graphical abstract: Image 1